Sistem Pendukung Keputusan Pemilihan Pegawai Terbaik dengan Menggunakan Metode Simple Additive Weighting (SAW) - Ismawati, Nunung; Wijaya , Dhina Puspasari; Pramuntadi, Andri; Danianti, Dita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
In human resource management, employee performance is one of the most important elements and must receive full attention from an organization. This is because employee performance is a determinant in achieving organizational goals efficiently and effectively. Therefore, every organization always strives to improve the performance of its employees in order to get the best employees according to the agency. This research develops a Decision Support System (SPK) for selecting the best employees using the Simple Additive Weighting (SAW) method at the Education, Youth and Sports Office (Dikpora) of Bantul Regency, Yogyakarta. The purpose of the research is to create an efficient and objective system in employee evaluation and selection. The SAW method was chosen for its simplicity and effectiveness in handling multi-criteria decisions. Employee performance is assessed based on criteria such as attendance, skills, teamwork, and loyalty, with weights according to their level of importance. This system is built with web technology using PHP, MySQL, and CodeIgniter framework. The results of this system can be accessed easily by users, providing transparency in the assessment process. Based on the results of the calculation, the employee with alternative A1 and obtained a score of 0.925% on behalf of (Albertus Dedi Susilo) became the first rank of the best employee.